Formulation and Antioxidant Activity of Peel Off Gel Mask from Paederia Foetida Extract - Reny Eka Evi Susanti; Qurrata Ayun (Program Studi Pendidikan Kimia FKIP Universitas Sebelas Maret, 2022)
The peel-Off gel mask is one of the unique characteristic forms of the mask that will form an elastic transparent film layer. It can be removed without rinsing after drying and leaving no residue. The manufacture of masks using natural material is better than synthetic materials as it can cause side effects and damage the natural shape of the skin. One of the natural materials that can be used as a natural ingredient mask is the Paederia Foetida leaf. Paederia Foetida leaf contains antioxidants beneficial as the antidote to free radicals. One of the antioxidants contained in the Paederia Foetida is a flavonoid compound. The research aimed to determine the best concentration of Paederia Foetida leaf extract in the formulation of pell off gel masks with high antioxidant activity. The research method consists of preparing the sample by macerating Paederia Foetida leaf powder using ethanol. Making peel-off gel mask with variation in concentration from Paederia Foetida leaf extract of 0%, 15%, 20%, 25%, 30%. mask quality test include organoleptic test, pH, Homogeneity, stability, Drying, and dispersibility—antioxidant activity test by using DPPH with expressed as IC50 concentration. The Result of the research is that Paederia Foetida leaf extract can be formulated into a peel-off gel mask stock. The formulation of a peel-off gel mask with a concentration of Paederia Foetida leaf extract of 20% was chosen because it meets the criteria of peel-off gel mask of Indonesian Nasional Standard (It is homogeneous and stable, pH 6, spreadability 6,5 cm, and dry time 28 minutes with an IC50 of 167.74 which is a weak antioxidant).